Clinical characteristics and treatment outcomes in Camurati–Engelmann disease: A case series. Issue 14 (April 2018) - Kim, Yoon-Myung; Kang, Eungu; Choi, Jin-Ho; Kim, Gu-Hwan; Yoo, Han-Wook; Lee, Beom Hee
Abstract: Background: Camurati–Engelmann disease is an extremely rare disease characterized by hyperostosis of multiple long bones. This condition is caused by heterozygous mutations in the TGFB1 gene. Methods: We describe the clinical and genetic characteristics of 4 Korean patients with this rare disease diagnosed at Asan Medical Center in Korea between June 2012 and May 2016, to increase awareness about this condition among general physicians and orthopedists. The presenting features, biochemical findings, radiographic and nuclear imaging findings, molecular analysis, and treatment outcomes of 4 patients were reviewed retrospectively. Results: Two patients had sporadic disease, whereas the other 2 were familial cases. The average age at symptom onset was 8.8 ± 5.5 (4–14) years. Symptoms included waddling gait or leg pain. Bone pain and easy fatigability were documented in all patients. Skeletal deformities such as osteoporosis, genu valgum, and severe scoliosis were observed. Visual and otologic manifestations presenting as exophthalmos, retinal detachment, and vestibulopathy were found in 3 patients. Skeletal survey showed diaphyseal expansion with diffuse cortical thickening of long bones in all patients. Bone scintigraphy images showed increased uptake of radioactive material in the calvarium and diaphysis of long bones. The mean erythrocyte sedimentation rate was 46.5 ± 22.2 (20–72) mm/h. Sequence analysis of TGFB1 revealed the previously reported mutations p.Arg218His, p.Arg218Cys, and p.Glu169Lys. Corticosteroid was effective in relieving pain, and losartan was used as maintenance therapy. Conclusions: Our experience suggests that this rare condition can be suspected in patients with characteristic symptoms and skeletal findings. Considering the presence of effective medical treatment, efforts are needed to identify more cases.